Ranking Tool Created for Medicinal Plants at Risk of Being Overharvested in the Wild - Castle, Lisa Marie; Leopold, Susan; Craft, Rachel; Kindscher, Kelly (Ethnobiology Letters, 2014)
We developed an adaptable, transparent tool that can be used to quantify and compare vulnerability to overharvest for wild collected medicinal plants. Subsequently, we are creating a list of the most threatened medicinal plants in temperate North America. The new tool scores species according to their life history, the effects of harvest, their abundance and range, habitat, and demand. The resulting rankings, based on explicit criteria rather than expert opinion, will make it easier to discuss areas of vulnerability and set conservation priorities. Here we present scores for 40 species assessed using the At-Risk Tool and discuss the traits that led to different scores for six example species: echinacea (Echinacea angustifolia DC. Asteraceae), peyote (Lophophora williamsii (Lem. ex Salm-Dyck) J.M. Coult. Cactaceae), sandalwood (Santalum spp. L. Santalaceae), stinging nettle (Urtica dioica L. Urticaceae), American ginseng (Panax quinquefolius L. Araliaceae) and mayapple (Podophyllum peltatum L. Berberidaceae).